Analisis Kinerja Keuangan PT. Blue Bird, TBK Indonesia Sebelum dan Saat Pandemi COVID-19 - Mochamad Ilham Aziz; Ade Momon (Peneliti.net, 2021)
COVID-19 causes a global pandemic that causes various human life settings to be affected in addition to health, especially the global economy. The transportation sector as one of the business sectors most affected by the COVID-19 pandemic, it is important to conduct periodic assessments of financial performance. This research aims to analyze the financial performance of PT. Blue Bird, Tbk which is a large non-online taxi fleet transport company with an assessment of liquidity ratio with Current ratio (CR), leverage ratio with Debt to Equity Ratio (DER), profitability ratio with Return On Assets Ratio (ROA), and activity ratio by calculating Receivable Turn Over (RTO). The method used is quantitative with descriptive approach and the data used is secondary data derived from the annual financial statements accessed on the Indonesia Stock Exchange through the official website. The results of the analysis obtained a decrease in revenue and profit up to almost 50% during the pandemic, an increase in liquidity ratio as much as 0.7 times during the pandemic, leverage ratio increased by 0.1 during the pandemic, profitability ratio decreased by 0.02 during the pandemic, and activity ratio, decreased by 0.17 during the pandemic.